Enhancing Productivity Potential of Saline Soil through Agroforestry System Using Saline Irrigation - Garg, Rakesh K.; Yadav, R. K.; Sheoran, Parvender; Kumar, Ashwani; Narjary, Bhaskar; Meena, M. D.; Sharma, D. K. (Indian Forester, 2017)
Establishing tree plantations on saline soil irrigated with saline ground waters may provide an economic use of abandoned lands, but a knowledge gap exists on potential of growing commercially important fast growing tree species under salt affected soils with saline irrigation and their impact on soil physico-chemical properties. The present study has been initiated to establish Melia composita and Eucalyptus tereticornis based agroforestry models and evaluate the performance of crops under trees and vice versa irrigated with the help of saline water irrigation. The treatments comprised of five tree and crop combinations viz., Eucalyptus tereticornis +crops, Melia composita +crops, Sole Eucalyptus tereticornis, Sole Melia compositaand sole crops i.e. pearlmillet and mustard under open conditions. Eucalyptus and Melia tree species recorded 78% and 70% survival, respectively. Growth performance of the two tree species was recorded one year after transplanting. Eucalyptus attained higher plant height (269.36cm) as compared to Melia (223.38cm) whereas diameter at breast height (DBH) was more in Melia (4.46cm) as compared to Eucalyptus (3.15cm). Longest branches, crown spread and number of branches were higher in case of Eucalyptusas compared to Melia. In general, declining growth trend was observed with increase in soil salinity. Mustard was sown as intercrop in between Melia and Eucalyptus rows. Germination of mustard crop showed variable response depending upon level of salinity. Germination percentage varied from nil (EC2 :7.28 dSm-1) to 85.0 (EC2:2.40 dSm-1) under Eucalyptus trees whereas it ranged from nil (EC2:7.29 dSm-1) to 70.0(EC2:2.40 dSm-1) under Melia trees. The average germination under Eucalyptus and Melia plantation was 27.91% and 2 30.42%, respectively. Results on growth parameters is also reported in this paper.